(untitled) (Jurnal Manajemen Bisnis, 2026)
This study investigates the effects of operational efficiency and business diversification on financial sustainability, with cash flow resilience as a mediating variable among 3 kg subsidized LPG stations in Bangkalan Regency. Using a quantitative explanatory design, data were collected through questionnaires from station owners/managers and analyzed using SEM-PLS. Results show that operational efficiency and business diversification positively affect cash flow resilience and financial sustainability. Cash flow resilience also significantly improves financial sustainability and partially mediates the relationships between both predictors and financial sustainability. The findings indicate that financial sustainability in regulated, low-margin micro-enterprises depends on efficiency improvements, diversified income sources, and disciplined cash flow management.